Interdigital Hyperplasia in Holstein Cattle Is Associated With a Missense Mutation in the Signal Peptide Region of the Tyrosine-Protein Kinase Transmembrane Receptor Gene - Zhang, Xuying; Swalve, Hermann H.; Pijl, René; Rosner, Frank; Wensch-Dorendorf, Monika; Brenig, Bertram (Frontiers in Genetics, 2019)
Bovine interdigital hyperplasia (IH) is a typical disease of the foot with varying prevalence depending on age, breed and environmental factors resulting in different degrees of lameness. In studies based on assessments of claw health status at time of hoof trimming and applying genetic-statistical models to analyze this data, IH consistently exhibits high estimates of heritability in the range of 0.30 to 0.40. Although some studies have identified chromosomal regions that could possibly harbor causative genes, a clear identification of molecular causes for IH is lacking. While analyzing the large database of claw health status as documented at time of hoof trimming, we identified one herd with extreme prevalence of IH of > 50 % of affected Holstein dairy cows. This herd subsequently was chosen as the object of a detailed study. A total of n = 91 cows was assessed and revealed a prevalence of 59.3 % and 38.5 % for IH cases, documented as ‘one-sided’ or ‘two-sided’, respectively. Cows were genotyped using the BovineSNP50 BeadChip. A genome wide association study revealed two significantly associated chromosomal positions (-log10P = 5.57) on bovine chromosome 8 (BTA8) located in intron 5 and downstream of the receptor tyrosine kinase-like orphan receptor 2 (ROR2) gene. As ROR2 plays a key role in ossification of the distal limbs and is associated with brachydactylies in humans, it was a reasonable candidate for IH. A comparative sequencing of the ROR2 gene between cases and controls revealed two missense variants in exon 1 (NC_037335.1:g.85,905,534T>A, ARS-UCD1.2) and exon 9 (NC_037335.1:g.86,140,379A>G, ARS-UCD1.2), respectively. Genotyping of both variants in the cohort of 91 cattle showed that the exon 1 variant (rs377953295) remained significantly associated with IH (p < 0.0001) as a risk factor of the disease. This variant resulted in an amino acid exchange (ENSBTAP00000053765.2:p.Trp9Arg) in the N-terminal region of the ROR2 signal peptide which is necessary for proper topology of the polypeptide during translocation. Quantification of ROR2 mRNA and ROR2 protein showed that the variant resulted in a significant suppression of ROR2 expression in homozygous affected compared to wild type and carrier cows.